2012
DOI: 10.3389/fendo.2012.00127
|View full text |Cite
|
Sign up to set email alerts
|

On the existence and function of galanin receptor heteromers in the central nervous system

Abstract: Galanin receptor (GalR) subtypes 1–3 linked to central galanin neurons may form heteromers with each other and other types of G protein-coupled receptors in the central nervous system (CNS). These heteromers may be one molecular mechanism for galanin peptides and their N-terminal fragments (gal 1-15) to modulate the function of different types of glia–neuronal networks in the CNS, especially the emotional and the cardiovascular networks. GalR–5-HT1A heteromers likely exist with antagonistic GalR–5-HT1A recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 79 publications
(127 reference statements)
6
50
0
1
Order By: Relevance
“…More recent studies demonstrating galanin receptor heteromers have introduced a further degree of complexity in interpreting galaninergic mechanisms in the brain (96). In addition to GALR1 and 5-HT1A receptor heterodimers (97), an involvement of the galanin (1-15) fragment in mood regulation via GALR1 and GALR2 heterocomplexes in the dorsal HPC and DR has been reported (98).…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies demonstrating galanin receptor heteromers have introduced a further degree of complexity in interpreting galaninergic mechanisms in the brain (96). In addition to GALR1 and 5-HT1A receptor heterodimers (97), an involvement of the galanin (1-15) fragment in mood regulation via GALR1 and GALR2 heterocomplexes in the dorsal HPC and DR has been reported (98).…”
Section: Discussionmentioning
confidence: 99%
“…GAL 2 also undergoes internalization upon ligand binding (Xia et al, 2004(Xia et al, , 2005b. There is also increasing evidence that different galanin receptors can form heteromers, at least in the CNS (Fuxe et al, 2012), leading to altered recognition of galanin ligands. Moreover, putative heteromers of galanin receptors with other GPCRs have been described, including GAL 1 with a 5-HT receptor, Y 1 and Y 2 (NPY) receptors, a 2 -adrenoceptor (Fuxe et al, 2008(Fuxe et al, , 2012, and dopamine D 1 -like receptors (D 1 and D 5 ), but not GAL 2 (Moreno et al, 2011).…”
Section: A Identification and Nomenclaturementioning
confidence: 99%
“…There is also increasing evidence that different galanin receptors can form heteromers, at least in the CNS (Fuxe et al, 2012), leading to altered recognition of galanin ligands. Moreover, putative heteromers of galanin receptors with other GPCRs have been described, including GAL 1 with a 5-HT receptor, Y 1 and Y 2 (NPY) receptors, a 2 -adrenoceptor (Fuxe et al, 2008(Fuxe et al, , 2012, and dopamine D 1 -like receptors (D 1 and D 5 ), but not GAL 2 (Moreno et al, 2011). This latter study provides strong evidence that D 1 -like/GAL 1 receptor heteromers integrate signals of the monoamine and neuropeptide transmitter systems to modulate hippocampal cholinergic neurotransmission.…”
Section: A Identification and Nomenclaturementioning
confidence: 99%
See 1 more Smart Citation
“…For example, a VT peptide can be modified or even split by ecto-enzymes (Konkoy and Davis, 1996) with the possible formation of different sets of fragments from the same parent peptide that can differentially modulate the various cells of CCNs eliciting different types of integrative responses (Agnati and Fuxe, 2000;Agnati et al, 2004aAgnati et al, , 2005cFuxe et al, 2007a). Fuxe et al (2012) suggested that galanin (1-15) can play a specific role in depression in view of its high diffusion capabilities [lower molecular weight with respect to galanin (1-29)] and hence its possible extra-synaptic modulatory actions on GalR-5-HT1A heteroreceptor complexes. Such a view underlines our proposal that GMN by regulating diffusion of VT signals in the ECS has a fundamental role in the brain holistic behavior.…”
Section: The Concept Of 'Lebensraum' and The Role Of Astrocytes In Itmentioning
confidence: 99%